Thorn Production Sdn. Bhd. / Shahida Azad Jamaludin ... [et al.] - Jamaludin, Shahida Azad; Ahmed, Shareenee; Shamsudin, Noraishah Mohammad; Marlizan, Salihin (Faculty of Communication and Media Studies, 2004)
Thorn Production Sdn Bhd was a small business started only by five people. Slowly this company had expand and been recognized by the entertainment industry in Malaysia. This company is a production house, which involved in production phases and gives services to clients. The objective is to make the entertainment industry in Malaysia rise and been recognized by the international.